2006
DOI: 10.1002/art.21725
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of activin receptor–like kinase 5 (transforming growth factor β receptor type I) signaling to the fibrotic phenotype of scleroderma fibroblasts

Abstract: Objective. To use a specific transforming growth factor ␤ receptor type I (TGF␤RI; activin receptor-like kinase 5 [ALK-5]) kinase inhibitor (SD208) to determine the role of activation of the TGF␤RI kinase (ALK-5) in maintaining the profibrotic phenotype of dermal fibroblasts in systemic sclerosis (SSc).Methods. The effect of SD208 on the expression of key biochemical markers of the fibrotic phenotype was compared in fibroblasts cultured from clinically involved (lesional) and clinically uninvolved skin of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
70
1
3

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 35 publications
11
70
1
3
Order By: Relevance
“…However, the complexity of the profibrotic effects of TGF␤ that involve both Smad3-dependent and -independent mechanisms presents a challenge in selecting appropriate therapeutic targets. For example, pharmacologic inhibitors of TGF␤RI kinase that result in blockade of Smad3 signaling (ALK-5 kinase inhibitors) did normalize elevated CCN2 levels in SSc fibroblasts and, in general, ameliorated only selected aspects of SSc fibrosis in vitro (35,36). Our study suggests that due to the pleiotropic nature of TGF␤ signaling, targeting a single component of the TGF␤ signaling pathway may not be effective in ameliorating SSc fibrosis.…”
Section: Smad1 Signaling Pathway In Ssc 2535mentioning
confidence: 74%
“…However, the complexity of the profibrotic effects of TGF␤ that involve both Smad3-dependent and -independent mechanisms presents a challenge in selecting appropriate therapeutic targets. For example, pharmacologic inhibitors of TGF␤RI kinase that result in blockade of Smad3 signaling (ALK-5 kinase inhibitors) did normalize elevated CCN2 levels in SSc fibroblasts and, in general, ameliorated only selected aspects of SSc fibrosis in vitro (35,36). Our study suggests that due to the pleiotropic nature of TGF␤ signaling, targeting a single component of the TGF␤ signaling pathway may not be effective in ameliorating SSc fibrosis.…”
Section: Smad1 Signaling Pathway In Ssc 2535mentioning
confidence: 74%
“…Prior reports have focused on general TGF␤ signaling pathway, including TGF␤ receptors and Smads, in the production and remodeling of ECM (Verrecchia and Mauviel, 2002;Verrecchia et al, 2006). However, it is now appreciated that selective modulation of profibrotic signaling downstream of TGF␤ would be beneficial in promoting and controlling the wound healing and scarring while leaving other effects of TGF␤ unaltered (Leask et al, 2003;Leask and Abraham, 2004;Chen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…TGF␤ also induces ECM synthesis and remodeling and myofibroblast differentiation (Leask and Abraham, 2004). Exaggerated TGF␤ signaling in fibroblasts contributes to chronic fibrosis (Chen et al, 2005(Chen et al, , 2006. The intracellular signaling pathway downstream to the TGF␤ receptors is mediated by the Smad family of transcription factors (Shi and Massague, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of this study, TGF␤1 stimulates col1 and col3 production by fibroblasts and is required for terminal differentiation of myofibroblasts during wound contracture (27). Furthermore, the pro-fibrotic effects of TGF␤1 on both normal and scleroderma skin-derived fibroblasts require signaling through ALK5 and phosphorylation of Smad2/3 (28,29). We have recently shown that TS5-mediated cleavage of aggrecan is required for the pro-fibrotic responses of synovium, meniscus, and cartilage in murine models of osteoarthritis (30) and also the fibrogenic phase of ligament repair in equine degenerative suspensory ligament desmitis (31).…”
mentioning
confidence: 90%